Chasing the Rainbow: Decoupled phenotypic and genotypic evolution in New Guinea’s rainbow skinks (Squamata: Scincidae) - Probst, Taylor; Frandsen, Paul B.; Whiting, Alison (Zootaxa, 2025)
With the advent of molecular data, the discovery of cryptic species has become commonplace. New Guinea, a region of high vertebrate biodiversity and complex geological history, has been found to contain immense numbers of cryptic skink species. We present the first molecular phylogenetic analysis of Carlia Gray, 1845, and its sister genus Lygisaurus de Vis, 1884, across mainland New Guinea and the Solomon Islands. We find rainbow skinks exhibit significant genetic divergence with minimal morphological variation and our data suggest the existence of many undescribed species. Due to the morphologically cryptic nature of rainbow skinks, we demonstrate the efficacy of the COI gene as a “barcode” for difficult species determinations. Divergence time and biogeographic analyses support four separate dispersal events from Australia to New Guinea for rainbow skinks from 10–5 mya, with most groups arriving first in the East Papua Composite Terrane (EPCT) and dispersing from there to other terranes and islands. Exceptions to this pattern were observed in Lygisaurus, which dispersed first to the West Papuan portion of the Craton 8.4mya, and the island clade of the Carlia fusca group, which dispersed to the Vogelkop peninsula 4.7mya and from there to many islands.